A COMPARISON OF THE CURRENT LEVEL OF THE SELECTED POWER ABILITIES OF JUNIORS IN TERMS OF PLAYERS' POSITIONS IN ICE HOCKEY - Rastislav Paľov, (Sport Scientific And Practical Aspects, 2025)
The aim of the study was to compare the current level of the selected power abilities of juniors hockey players between defenders and forwards (n = 20, height = 182.3±4.9 cm, weight = 81.5±6.7 kg, age = 18.44±0.70 years; defenders = 8, height = 184.0±3.8 cm, weight = 84.2±6.5 kg, age = 18.60 years ±0.59; attackers = 12, height = 181.2±5.4 cm, weight = 79.6± 6.7 kg, age = 18.33±0.77 years) in a competitive year 2014/2015. The indicators of selected power abilities were observed by three tests: 1. 3 hop jump on one foot from the place, 2. Sit up and 3. Weights on the bench press with 70% of its own weight. Statistical analysis was conducted by using the software IBM® SPSS® Statistics V19. The average value of the test The average value of measurement for 3 hop jump on one foot from the place (left leg) of the research file was 473.6±32.26 m the best recorded time was 512 m, the lowest time was 417 m. The difference between defenders and forwards was statistically significant (U = 30, Z = -1.93, p <0.05, r = 0.31 – medium effect). The average value of measurement for 3 hop jump on one foot from the place (right leg) of the research file was 479.9±39.12 m the best recorded time was 565 m, the lowest time was 424 m. The difference between defenders and forwards was statistically significant (U = 26.5, Z = -1.66, p < 0.05, r = 0.37 – medium effect). In the test Sit up, the average value of the whole file was 69.10±7.53 repeat. For the defenders, the average finish time indicated of the value 69.5±8.77 repeat and for forwards 68.83±6.79 repeat, which again is statistically significant difference in favor of the defenders (U = 41.5, Z = -0.5, p < 0.05, r = 0.11 – small effect). The average value of the test Weights on the bench press with 70% of its own weight of the whole file was 21.7±4.23 repeat, among defenders was 25.5±2.67 repeat, among forwards 19.17±3.01 repeat, which is a statistically significant difference between defenders and forwards (U= 5.5, Z = -3.3, p < 0.05, r = 0.74 – large effect) in favor of the defenders.